EFFECT OF WATER-RETAINING POLYMERS ON INFILTRATION OF WATER INTO SOIL - PREVEDELLO, Celso Luis; LOYOLA, Jocely M. Thomazoni (Scientia Agraria, 2007)
With the objective of evalulating the effect of water-retaining polymers on the infiltration capacity and the depth reached by the wet front in two different porous media, one of a clay nature and the other of a beach sand, experiments in laboratory were performed. The polymer concentrations used were 0; 4 and 8 kg m-3. The results showed that the polymers did not affect either the infiltration capacity or the depth reached by the wet front when the infiltration times were relatively short and the polymers were dry at time zero. For long periods of infiltration, when the polymers were completely hydrated, the rate of infiltration was reduced 13-fold, but only in the clay-based porous medium. The absence of effects in the sandy medium could not be explained.